Formal Methods for Dynamical Systems 13th International School on Formal Methods for the Design of Computer, Communication, and Software Systems, SFM 2013, Bertinoro, Italy, June 17-22, 2013. Advanced Lectures - Bernardo, Marco; Vink, Erik.; Pierro, Alessandra; Wiklicky, Herbert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book presents 5 tutorial lectures given by leading researchers at the 13th edition of the International School on Formal Methods for the Design of Computer, Communication and Software Systems, SFM 2013, held in Bertinoro, Italy, in June 2013. SFM 2013 was devoted to dynamical systems and covered several topics including chaotic dynamics; information theory; systems biology; hybrid systems; quantum computing; and automata-based models and model checking.
Chaotic dynamics -- Information theory -- Systems biology -- Hybrid systems -- Quantum computing -- Automata-based models and model checking.
Keywords: Computer science; Software engineering; Logic design; Bioinformatics; Computer Science; Software Engineering; Logics and Meanings of Programs; Computational Biology/Bioinformatics.; Computation by Abstract Devices